'EMS needs revolution not evolution'. (17th February 2023) - Williams, Rob
Abstract: Rob Williams argues that the current structure of EMS, even accounting for the RCVS's proposed changes, is an outdated model not fit for purpose, and that it is time for a complete rethink.